Numerical Analysis of the Influence of Clearance on Stress State and Contact Pressure in Plain Bearings - Vasile Cojocaru; Calin-Octavian Miclosina (Robotica & Management, 2017)
In the analysis of plain bearings by finite element method it is important to model as closely to real state the aspects that influence the stress and contact pressure: the loading mode, the properties of the materials, the lubrication system, the clearance between the shaft and the bearing body, the evolution in time of clearance correlated with the wear, etc. In order to study the effect of the clearance on the stress state, a plain bearing with nominal diameter d=40 mm was modeled. The contact pressure and the equivalent stress were computed for six discrete values of clearance, range from c=0 to c=0.3 mm. It has been shown that the increase of clearance generates an increase of the equivalent stress and contact pressure. The growth rate is higher for contact pressure, due to the decrease of the contact surface between the shaft and the bearing body.